Progression in skill training - Luhtanen, P. (coachesinfo.com)
It is difficult to build up any perfect and progressive classification or taxonomy of individual skills in football, but it is easy to get ideas and tools for beginning to construct it. This taxonomy is multidimensional and includes continuums or factors which are always influencing the total performance. Let's take an example from striking. Highly skilled players can predict the ball contact points with such precision that successful plays and strikes at the ball can be made without looking at it just before the ball contact. Of course they are not doing so all of the time due to the close attention by opponents or due to the maximal performance. The question is how to develop a talented junior player to be a highly skilled senior player as mentioned above? What could be the progressive training plan for him, if we take into consideration all the factors including the development and the individual striking skills (Generally striking skill could be defined as a combination of four different changing factors in the game as follows: striking skill = player x ball x environment x target).